Sarcophaga (Hoa) flexuosa Ho (Diptera: Sarcophagidae): association of sexes using morphological and molecular approaches, and a redefinition of Hoa Rohdendorf - Zhang, Dong; Zhang, Ming; Pape, Thomas; Gu, Cai-Wei; Wu, Wei (Zootaxa, 2013)
Sarcophaga flexuosa Ho, 1934 is the type species of the currently monotypic genus-group taxon Hoa Rohdendorf, 1937, which here is considered a subgenus of Sarcophaga Meigen, 1826. Using DNA sequences of mitochondrial genes (cyto-chrome oxidase I and cytochrome b), we positively identify, for the first time, the female of S. (H.) flexuosa. The female is described, the male is redescribed, and both sexes are illustrated using a combination of line drawings, photographs and scanning electron microscopy images. It is argued from the morphology of the male terminalia that Sarcophaga flexuosa is the sister taxon of Sarcophaga basiseta Baranov, 1931, and the subgenus Hoa is redefined to include both of these spe-cies.